My Student Cannot Wait! Teaching Tolerance Following Functional Communication Training. (August 2019) - Muharib, Reem; Pennington, Robert C.
Functional communication training (FCT) involves the reinforcement of an appropriate communicative response as an alternative to challenging behavior. The intervention has been identified as an evidence-based practice across multiple populations. Despite its extensive research support, FCT may be impractical in some educational settings because it often requires educators to reinforce alternative responses at high rates. In this discussion article, we describe three procedures (delay to reinforcement, chained schedules of reinforcement, and multiple schedules of reinforcement) that can be used following FCT in educational settings to teach students who exhibit challenging behaviors to tolerate waiting for a reinforcer.